Tres Pas a feasibility study - Asis, Reina; Deluso, Felomina; Honrado, Darlene; Hortillo, Royce; Lapastora, Marivie; Omena, Josie; Pojol, Mae.; Tala, Stephen Dublon; Villar, Mylitte
Executive Summary-Proponents' Description - Entertainment and leisure are basic needs of man. Like food and shelter it is necessary in his temporal existence. To quote "all work and no play makes a person dull". Besides, what is the purpose of having too much money when you can not enjoy it. This the motivation which drive the proponents to pursue the evaluation of the viability of Tres pas' operations-providing an alternative but quality entertainment to customers at reasonable prices. Moreover, the rapid increase in population as well as the boom of the night entertainment industry in iloilo City helped the proponents to continue this study. Nine accountancy graduates of the University of the Philippines in the Visayas facilitated the detailed assessment of the project. They are Royce Hortillo, Darlene Hondrado,Ivie Lapastora, Josie Omena, Mae Pojol, Felomina Deluso, Reina Asis, Mylitte Villar, and Stephen Tala. Their skills derived from academic and practical knowledge shall equip them to successfully run the business organization. Each partner will contribute an equal amount of share for the capital of the business. This can either come from the personal funds or from borrowings. However, this matter will be a personal transaction of the partners and is distinct from any business transactions. Loans from banks and other financial institutions will not be transacted within 3 years from the date the business operation will commence. This is due to the fact that it is hard to get outside financing in cases wherein a business is just starting. If ever a loan is required, a considerable amount will be paid because of a high interest rate. But when the business will begin to stabilize, transacting for loans will be an alternative in financing the growing capital needs of the company. The business operations will be managed by 3 partners, namely : Stephen Tala, Felomina Deluso, and Mylitte Villar. The company will hire a Marketing manager to be-in-charge of the Marketing division. The other one will be in-charge with the personnel division and the remaining partner will be in-charge of the Finance division. Each of them will contribute an amount of P450,000.00 coming from their personal savings. Business dealings of Miss Darlene Hondrado, being the wealthiest partner will furnish an amount of p450,000.00 to the partnership. Miss Mae Pojol recently sold a portion of her vast tracts of land to a charitable institution. A portion of the proceeds amounting to P450,000.00 will be invested in the partnership. Miss Royce C. Hortillo is now happily married to a Korean business tycoon. She will provide an equal amount of money. Miss Josie Omena, a Muslim princess whose lineage can be traced from the sultans of Brunei, acquired the National Power Corporation single-handedly. She will contribute P450,000.00 to the partnership. Lastly, Miss Marivie Lapastora, the only Filipina who had once defeated the then unknown Martina Hingis in the U.S. Ope, will provide P450,000.00 coming from the cash prize she had received in the said tournament. Description of the Project - Tres pas. This will be the name of the establishment. Tres, means three, since it provides three kinds of entertainment, and pas, meaning the right of precedence. the first to be chose by the customers among existing entertainment places. It will have its operations in Brgy. Bolilao, Mandurriao, Iloilo City. The fact commercialization of the area will give the company competitive advantage over other competitors. Tres pas will be divided into two main sections. The first section will handle the videoke bar operations. The second one will be the place for the discohouse. However, on Sundays, Mondays and Wednesdays, the discohouse will be converted into a music bar where a live band is expected to perform. Quality food at reasonable prices will be served and drinks may be customized to answer the whims and preferences of the customers. Fast service delivered by courteous personnel will be a main focus of the company's operations. Continuous improvement of services rendered will be undertaken. Thus, providing its market a venue for sound entertainment. Summary of findings & conclusions per aspect 1) Market Aspect - as shown in the computations, the market study provided a quantitative evidence on the existence of an unfilled market. This excess in demand is further widened by the rapid increase in the population of professionals and students in Iloilo City. Thus, Tres pas will readily capture a position of the market that will give the business a sure amount of revenue every year. The supply of raw materials needed far exceeds its demand. This is due to the fact that Iloilo is rich in marine, livestock and other agricultural resources. A marketing strategy was developed to enter and capture a certain portion of market. Therefore, the market study of putting up Tres Pas is feasible. 2) Technical Aspect - the technical study showed that there is a considerable number of suppliers for the needed materials, inputs, facilities, equipment and other supplies. Furthermore, accessibility to these suppliers is not a problem since most of them, if not all, are within Iloilo city. The labor and other technical skills necessary in the operations is also available. Proposed operations was accomplished. Plant location, its design and other requirement and its compliance with government policies and regulations were studied and done. From this, a conclusion can be derived - the technical aspect is feasible. 3) Management Aspect - the organization will adopt the partnership form. This is mainly due to ease of formation and accumulation of capital. The organizational structure will be divided into 3 divisions : personnel, marketing and finance. The positions can readily be filled up although training, experience and academic qualifications are necessary. The salaries and wages to be paid are slightly higher compared t the industry level in order to attract quality personnel. Due to the ample supply of personnel required, the management study if feasible. 3) Management Aspect - The organization will adopt the partnership form. This is mainly due to ease of formation and accumulation of capital. The organizational structure will be divided into 3 divisions : personnel, marketing and finance. The positions can readily be filled up although training, experience and academic qualifications are necessary. The salaries and wages to be paid are slightly higher compared to the industry level in order to attract quality personnel. Due to the ample supply of personnel required, the management study is feasible. 4) Financial Aspect - the technical study presented the various financial statements and the analysis of its results. Assumptions had been initially made before the said financial statements were constructed to provide basis for the projections. These assumptions had been made as conservative as possible and in accordance with the actual situation. The project was profitable throughtout the projected 5 year period and investment may be recoovered for 3 and 6 months. Thus, the project is found to be financially viable. 5)Social Desirability - aside from its objective of generating revenues, Tres Pas aims to serve the growing demand of the Ilonggos for a place of sound entertainment. A place where they could relax, even improve their singing and dancing skills and be in company of people who also want to enjoy themselves. In order to maintain such atmosphere, Tres pas is highly aware of its social responsibility. The company's management undertakes to give back at least something beneficial to the Society Development of the community where it is situated will be one of its main concern. The company's management will see to the maintenance and cleanliness of the environment (e.g. proper waste disposal, recycling of the materials, etc.). Sanitation and security of the place will also be components of the company's policy (e.g. safe drinking water, sanitary kitchen and dbathroom, dependable guards, etc.). Activities and shows will also be sponsored which could promote welfare of the public. One of the company's policies emphasizes on maintaining its respectablity. To promote this image, Tres Pas would only provide decent shows, hire employees with good moral character and impose strict adherence to the regulations and policies of the company (e.g. dress code, peace and order policy, etc.). The company's management assumes the exemplary role in upholding the respectable image of the organization and will see to it that customer relationship would only be up to a professional level from among the management's rank, as well as, from its employees. Suggestive dressing and deeds from the employees and also from its management would be against the policy. Furthermore, the establishment of a business enterprise in the locality will provide more jobs especially to the nearby residents of the company's vicinity. Local bands, for one, will be given the chance prove their performer's capabilities. Taxes to be paid upon opration can also raise revenue for the city which could provide additional income to be used for public purposes. The construction would also encourage more businesses to operate in the place, thus, enhancing economic growth in the locality.
Feasibility study (BA129 - Management Advisory Services) -- Iloilo City : University of the Philippines in the Visayas - College of Management, [n.d.].